INVENTARISASI KUPU-KUPU DI UNIVERSITAS NEGERI MEDAN - Siregar, Elida Hafni; Simatupang, Halim (Program Studi Biologi, Fakultas Biologi Universitas Medan Area, 2017)
This reseach aims to known the butterflies species at State University of Medan. Observation and collection ofÂ butterfliesÂ were conducted from March â April 2016 at State University of Medan. Butterflies observationÂ conducted with scan sampling method at 09:00 to 17:00 in sunny days. This study consist ofÂ found 43 species of butterflies, belonging to 5 families, i.e. Pieridae, Papilionidae, Nymphalidae, Lycaenidae, and Hesperiidae. 15 species of butterflies are found in only one site but 2 species are found in all sites, i.e. Appias olferna and Papilio polytes.